Phenotypic and Immunometabolic Aspects on Stem Cell Memory and Resident Memory CD8+ T Cells - La Manna, Marco Pio; Shekarkar Azgomi, Mojtaba; Tamburini, Bartolo; Badami, Giusto Davide; Mohammadnezhad, Leila; Dieli, Francesco; Caccamo, Nadia (Frontiers in Immunology, 2022)
The immune system, smartly and surprisingly, saves the exposure of a particular pathogen in its memory and reacts to the pathogen very rapidly, preventing serious diseases. Immunologists have long been fascinated by understanding the ability to recall and respond faster and more vigorously to a pathogen, known as "memory". T-cell populations can be better described by using more sophisticated techniques to define phenotype, transcriptional and epigenetic signatures and metabolic pathways (single-cell resolution), which uncovered the heterogeneity of the memory T-compartment. Phenotype, effector functions, maintenance and metabolic pathways are helpful in identifying these different subsets. Here, we examine recent developments in the characterization of the heterogeneity of the memory T cell compartment. In particular, we focus on the emerging role of CD8+ TRM and TSCM cells, providing evidence on how their immunometabolism or modulation can play a vital role in their generation and maintenance in chronic conditions such as infections or autoimmune diseases.